Patientś experiences of patient education on psychiatric inpatient wards; a systematic review. Issue 3 (March 2018) - Kristiansen, S.T.; Videbech, P.; Kragh, M.; Thisted, C.N.; Bjerrum, M.B.
Highlights: Systematic patient education programs are reported useful when taking into account patientś individual situations. Patients with serious mental disorders prefer patient education through different educational sources. Patients with serious mental disorders wish for flexible patient education programs tailored the needs of the patients. Abstract: Objective: To synthesize the evidence on how patients with serious mental disorders perceived patient education on psychiatric wards and to learn more about the patient perceived benefits and limitations related to patient education and how well patient education meets the perceived needs of inpatients. Methods: Quantitative and qualitative data were categorized and synthesized. A systematic literature search was conducted. Articles were validated using validated critical appraisal tools. Data were analyzed using inductive content analysis. Results: Five articles met the inclusion criteria. The results concerned the specific population with bipolar disorder or schizophrenia. Two explanatory syntheses were aggregated: (I) Benefits and perceived barriers to receiving education and (II) Educational needs of mental health patients. Patients reported mechanical information dissemination and lack of individual and corporative discussions. Patients preferred patient education from different educational sources with respect to individual needs. Conclusion: Patient education were most useful when it could be tailored to an individuaĺs specific needs and match patient preference for how to receive it. The findings did not provide evidence to support any educational methods of preference. Practice implications: The findings may contribute to the development of educational interventions that are perceived more helpful for in-patients suffering from serious mental disorders.